COMPOSITION AND AGE CLASS OF LONG-TAILED MACAQUE (MACACA FASCICULARIS) IN THE TROPICAL PEAT ECOSYSTEM (CASE: In Buffer Village Around Orang Kayo Hitam Forest Park) - Yoannisa Egeustin; Dian Iswandaru; Christine Wulandari; Novriyanti Novriyanti; Hendra Prasetia (Jurnal Belantara, 2023)
The long-tailed mcaque (Macaca fascicularis) has a fairly wide population distribution in Indonesia. According to IUCN data, the population of long-tailed mcaque is decreasing every year, the cause is a decrease in habitat quality. One of the habitats of long-tailed mcaque which is currently under pressure due to conversion is located in a buffer village around the Orang Kayo Hitam Forest Park (Tahura OKH). This study aims to analyze the composition and age class of long-tailed monkeys. Observation methods were used to observe long-tailed mcaque based on morphological characteristics such as coat color and body size. Based on the results of the study, the composition of long-tailed mcaque was divided into two groups, the residential group (KP) and the river border group (KS). The number in KP is 8 individuals with an age class of 5 adults, 3 immature while the number in KS is 27 individuals with an age class of 18 adults, 4 immature, 3 juvenile, 1 infants. This condition illustrates that the river border habitat is better than the residential habitat. In addition, adults and adolescents are more numerous, indicating individuals who have a function for reproduction and continue reproduction. This breeding rate is the potential for regeneration of long-tailed mcaque and the potential for the regeneration process of peat ecosystems through the role of long-tailed monkeys as pollinators for seed dispersal.